Formulation and Effectiveness Test of Starfruit Extract Shampoo (Averrhoa bilimbi L.) Against Mortality Pediculus humanus capitis - Intan Kurnia Putri; Maya Uzia Beandrade; Regina Ananda; Reza Anindita (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
One of the skin infections that cause health problems in children is pediculosis capitis, which is caused by head lice (Pediculus humanus capitis). One of the efforts to prevent pediculosis can be by testing the formulation of an anti-head lice shampoo using the natural ingredient of star fruit (Averrhoa bilimbi L), which contains flavonoid compounds, alkaloids, and saponins. The purpose of this study was to determine the physical stability and effectiveness of the killing power of anti-head lice shampoo preparations with variations in the concentration of star fruit extract formula 1 (F1) 1.5%; formula 2 (F2) 2%; and formula 3 (F3) 2.5% against head lice Pediculus humanus capitis. This type of research is a mixed method (quantitative and qualitative) with an experimental design. The variation in the head lice anti-head shampoo formula is F1 1.5%, F2 2%, and F3 2.5%. Phytochemical screening tests include flavonoid compounds, alkaloids, and saponins. Physical stability tests were carried out for four weeks, including organoleptic, homogeneity, pH, viscosity, and foam height. The lethality test was carried out on the head lice of Pediculus humanus capitis. The data analysis is descriptive and comparative with the One Way ANOVA test. The phytochemical screening test of star fruit extract obtained positive results for flavonoids, alkaloids, and saponins. The organoleptic test of F1 shampoo 1.5%, F2 2%, and F3 2.5% showed white, thick results and a distinctive lemon aroma. The viscosity test was F1 1.5% (2,007-2,020 cP), F2 2% (2,020 cP), and F3 2.5% (2,020 cP). The homogeneity test obtained homogeneous results in all three formulas. The results of the foam height test were F1 1.5% (7.17-9.50 cm), F2 2% (7.67-9.83 cm), and F3 (7.83-9.80 cm). The results of the One Way Anova test showed a significance value of 0.012 < 0.05, or there was a significance influence of the shampoo formula of F1 1.5%, F2 2%, and F3 2.5% against the pH value of head lice anti-head shampoo stored for four weeks. The shampoo of star fruit extract affected the death of head lice for 10 minutes with an effective formula at a concentration of 2.5%. The physical evaluation of the head lice shampoo preparation showed good stability. The comparative test results showed that the pH of the shampoo preparation stored for four weeks could be unstable.